2022
DOI: 10.1155/2022/6263423
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gastric Microorganisms Other than Helicobacter pylori in the Development and Treatment of Gastric Diseases

Abstract: The microenvironment in the stomach is different from other digestive tracts, mainly because of the secretion of gastric acid and digestive enzymes, bile reflux, special mucus barrier, gastric peristalsis, and so on, which all contribute to the formation of antibacterial environment. Microecological disorders can lead to gastric immune disorders or lead to the decrease of dominant bacteria and the increase of the abundance and virulence of pathogenic microorganisms and then promote the occurrence of diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 112 publications
0
12
0
Order By: Relevance
“…( Bakhti and Latifi-Navid, 2021 ). At the genus level, Helicobacter and Haemophilus increase while Rosette decreases ( Duan et al., 2022 ). This phenomenon further shows that H. pylori has advantages over other flora.…”
Section: Effects Of H Pylori Infection On Gastroin...mentioning
confidence: 99%
“…( Bakhti and Latifi-Navid, 2021 ). At the genus level, Helicobacter and Haemophilus increase while Rosette decreases ( Duan et al., 2022 ). This phenomenon further shows that H. pylori has advantages over other flora.…”
Section: Effects Of H Pylori Infection On Gastroin...mentioning
confidence: 99%
“…Several studies have shown that Candida colonization of the gastric mucosa is associated with several gastric pathologies. Moreover, the co-existence of Candida species and H. pylori has been confirmed in several studies and a synergistic relationship between these two microorganisms in the pathogenesis of gastric diseases has been suggested [ 16 , 24 ]. Based on this long-standing relationship between the presence of Candida and H. pylori , we hypothesized that Candida presence in the gastric compartment could contribute not only to H. pylori pathologies but also to the resistance to the applied antibiotic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, H. pylori has been considered the only true inhabitant of the human stomach. However, despite the harsh environmental conditions, the existence of a thriving and dynamic gastric microbial community has been proven [ 24 , 25 , 26 , 27 ]. It is estimated that the stomach is inhabited by 10 2 –10 4 colony-forming units ( CFU )/mL [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical literature is full of data about H.Pylori mono infection treatment and Clostridium Difficilis mono infection treatment [7]. Furthermore, there are many researches about Clostridium Difficilis infection following H.Pylori eradication treatment [8]. However, there is paucity of information on Clostridium Defficilis and H.Pylori co infection.…”
Section: Introductionmentioning
confidence: 99%